2022
DOI: 10.3390/ijerph19063649
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Alexithymia and Mental Health Is Fully Mediated by Anxiety and Depression in Patients with Psoriasis

Abstract: Background: Psoriasis is a common skin disease that affects quality of life, especially mental health. Alexithymia has been considered a relevant feature in psoriasis patients. Moreover, psoriasis was found to be associated with negative psychological health, including anxiety and depression. As the pathways linking alexithymia and mental health remain unclear among patients with psoriasis, we aimed to examine the mediating role of anxiety and depression in the relationship between alexithymia and mental healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 49 publications
(76 reference statements)
1
10
0
Order By: Relevance
“…The HADS was used to evaluate the overall mood, which has the advantage of assessing depression and anxiety using the same metric. 18,30 We investigated the potential link between the numbers of AEs or involved systems/ tissues and the HADS-Anxiety and HADS-Depression scores via the use of linear regression models. Although there were no significant changes in the HADS scores after acitretin treatment, the treatment-related AEs had some effects on psychological aspects such as anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%
“…The HADS was used to evaluate the overall mood, which has the advantage of assessing depression and anxiety using the same metric. 18,30 We investigated the potential link between the numbers of AEs or involved systems/ tissues and the HADS-Anxiety and HADS-Depression scores via the use of linear regression models. Although there were no significant changes in the HADS scores after acitretin treatment, the treatment-related AEs had some effects on psychological aspects such as anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%
“…Several articles found that one's emotional or psychological state contributed to mental health conditions (52,119,(129)(130)(131)(132)(133). Positive feelings such as hope, optimism, and self-efficacy were generally associated with better mental health status than helplessness, pessimism, worry/fear, distress, and anxiety (129,131,134,135).…”
Section: (Which Was Not Certified By Peer Review) Preprintmentioning
confidence: 99%
“…Psoriasis has been considered one of the most stress-related skin diseases, and its onset or recurrence is connected with stress markers (Cannavò et al, 2019;Hunter et al, 2013) and the relationship between stress and the exacerbation of the symptoms (Rousset & Halioua, 2018). Psoriasis has been related to a more significant presence of alexithymic traits (Quinto et al, 2022), sympto-matology related to higher levels of stress (Baker et al, 2013), and has been associated with depression (Pietrzak et al, 2017), anxiety (Fleming et al, 2017), and suicidal ideation (Cohen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%